Horizontal mergers and uncertainty - Nicolas Le Pape; Kai Zhao (Kiel Institute for the World Economy (IfW), 2013)
Some path-breaking work on mergers takes efficiency gains for granted, or assumes that firms have perfect knowledge when taking merger decisions. In practice, firms and competition authorities cannot know exact future efficiency gains, prior to merger consummation. This paper analyzes horizontal mergers when the output decision-making process is sequential. A key assumption is that mergers create uncertainty on productivity and informational asymmetry between firms. The paper also studies whether the merged firm has interest to reveal the information about its own cost to competing firms. In terms of Merger Approval, the paper emphasizes the timing of regulatory intervention and distinguishes two different merger control interventions (ex ante or ex post enforcement). Since prudent competition authorities (using ex ante intervention) should take the restrictive policy, the framework illustrates why US Horizontal Merger Guidelines and EC Merger Regulation are biased in favor of the consumers' interests.
Keywords: D21; D80; L20; L40; 330; merger; competition authorities; uncertainty; asymmetric information